Thoracic Vertebral Fracture in a Female Case of Ankylosing Spondylitis Complicated with Turner Syndrome and Insufficient Response to Adalimumab - Lin Wen; Jinxian Huang (Journal of Clinical Rheumatology and Immunology)
Background: Ankylosing spondylitis (AS) is a chronic disease characterized by inflammatory back pain, with osteoporosis prevalence ranging from 18.7% to 62% 1. Vertebral fractures are four times more likely to occur 2. Turner syndrome (TS) is the most common sex chromosome abnormality in females, with a 1.4- to 2.2-fold increased likelihood of osteoporosis-related fractures 3. Seven cases of AS combined with TS with HLA-B27 positivity have been reported4. Methods: We report a case of a female patient with AS and TS who exhibited an inadequate response to adalimumab (ADA) and suffered a thoracic vertebral fracture. Results: A 41-year-old woman with HLA-B27 negative was diagnosed with AS in 2012 because of low back pain, and began ADA treatment in 2018. The patient had a past history of TS (45X/47XXX) with ultrasound revealing smaller than normal ovaries and uterus. Body weight was 54kg and height was 145cm (BMI25.68). She had primary amenorrhea, a wrist fracture at a young age, and a thoracic spine fracture in 2018. Bone mineral density (BMD) values for orthotopic lumbar vertebrae L1-L4 were 0.74 g/cm2, with Z-score of -2.7, and 0.564 g/cm2 at the left femoral neck with Z-score of -2.4. The FRAX tool predicted a 10-year fracture risk of 2.4% for the occurrence of major osteoporotic fracture (MOF), and a fracture risk of 0.9% for hip fracture. She initiated hormone replacement therapy (HRT). In November 2022, she discontinued ADA due to COVID-19 infection. Laboratory tests identified slightly elevated inflammatory markers (Fig. 1), low trough drug level of 0.31ug/ml and positive anti-drug antibody. In February 2023, she slipped in a snowdrift and experienced increased back pain. Spinal MRI revealed osteoporosis with a T7 compression fracture and a new T9 fracture (Figure 2 A,B). Sacroiliac (SI) joints MRI showed significant improvement of inflammation (Fig. 2 C,D). Spine surgery consultation suspected fracture attributed to obvious kyphosis deformity and stress concentration during falls, resulting in buckling compression. Repeated test determined a BMD value of 0.920 g/cm2 for orthotopic L3-L4 with a Z-score of -1.4, and a BMD value of 0.775 g/cm2 for the left total hip with a Z-score of -1.2, the 10-year probability of MOF was 3.2%, and that of hip fracture was 0.5%. She was diagnosed with severe osteoporosis due to recurrent fracture despite of BMD improvement and anti-osteoporosis medications were postponed. Conclusion: This case further proved the dominant role of disease co-morbidity and insufficient treatment in the unfavorable outcome regardless of genetic predisposition.